Os desafios para a efetivação do direito à consulta prévia, livre e informada: uma análise de sua aplicação no caso expansão minerária sobre territórios tradicionalmente ocupados por quilombolas em Oriximiná, Pará - RIBEIRO, Júlia de Sousa Farias (Universidade Federal do Oeste do Pará, 2024)
The goal of this work is to analyze the right to prior, free, and informed consultation as well as its application in the case of mining expansion over territories traditionally occupied by Quilombola communities in the municipality of Oriximiná, in the State of Pará. The a im is to conduct a case study of the conflict generated by the dispute over the territory claimed by those communities in view of the bauxite exploitation, analyzing the challenges encountered by them to implement the right to prior consultation. Through the civil inquiry initiated by the Federal Public Ministry of Santarém and the data collected by an under graduate scientific research carried out in 2017, we investigate whether the prior consultation was applied according to international parameters in the event mentioned and define what challenges these communities face for the establishment of such right. In this way, the text is divided in three parts: the introduction where we make an historical approach to the communities in the quarrel for natural resources in the region since the implementation of the company Mineração Rio do Norte in the 1970s, until the formalization of the contend through the inquiry previously acknowledged by the Federal Public Ministry, highlighting the nodal points in the dispute; in the second part, we debate the conflicts arising from these nodal points thus building the necessary legal basis for the topic’s discussion, and also highlighting the points of conflict or doubts about the application of prior consultation, and the way that literature as well as international jurisprudence face each of these divergences; finally, we discuss the challenges for the establishment of the right to prior consultation considering aspects of its regulation in the country and the role of community’s participation through the autonomous consultation protocols. In conclusion, we observed that even with the right’s recognition by the State, private sector companies, non-governmental organizations and the Public Ministry communities from Alto Trombetas did not consider that the consultation process has in fact occurred. Revealing there are still countless doubts regarding the application of this right in specific cases which can be overcome by the assembly and application of consultation protocols.